Novel combination therapy for respiratory diseases of small ruminants: Field studies of over 10 years - Gholami, Mohammad Hossein; Derakhshanfar, Amin; Gholami, Tahereh (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study aimed to evaluate a new drug combination for small ruminant respiratory diseases to find a better treatment protocol for the potential replacement of older methods. Materials and Methods: A total of 6,886 animals received common respiratory disease therapies out of 15,845 animals that had respiratory disorders. The new combination therapy technique treated the remaining animals (8,968). The animals were given an oral suspension of triclabendazole or levamisole at an initial dosage of 0.2 ml/kg body weight (BW). The following day, 0.2 mg/kg of 1% ivermectin was subcutaneously administered. Then, on the third and fifth days of treatment, a subcutaneous injection of 30 mg/kg BW of florfenicol (30%) was administered. The survival and recovery rates for both groups were tracked throughout a 6-month period of observation. Postmortem and histopathological signs were also assessed. Results: In the group of the novel combination therapy, group A, clinical, postmortem, and histopathological signs were significantly reduced compared to group B. Clinical signs and mortality in group A were 90% and 93% lower than in group B, respectively. Animals that received the new combination therapy were healed of their disease and stayed immune for 6 months. Conclusion: This novel therapy demonstrated significant efficacy against respiratory diseases in a 10-year field study. The paper proved that the protocol introduced could be a new therapeutic approach. J. Adv. Vet. Anim. Res., 10(3): 516–521, September 2023 http://doi.org/10.5455/javar.2023.j705